ChemInform Abstract: Relay Catalysis Using a Gold(I) Complex/Broensted Acid Binary System for the Synthesis of Bezoxasiloles. Issue 41 (7th October 2014) - Horino, Yoshikazu; Takahashi, Yu; Nakashima, Yuichi; Abe, Hitoshi
Abstract The novel strategy for the synthesis of benzoxasiloles involves a cascade intramolecular allylation of alkynes and the addition of silanols to enones.